Cuadrar el ciclo: retos de la Declaración de París para la planificación estratégica de las agencias de cooperación - Alcalde, Ana R.; Moreno, Almudena (Revista Española de Desarrollo y Cooperación, 2023)
In this article, the authors describe the main consequences of the Paris declaration on aid´s effectiveness in the strategic planification of the international cooperation for development. Then they show what measures must be taken by the donors in order to incorporate the five principles included in this agreement